THE VALUE OF THE STUDIES OF THE METHODICAL ERROR OF DISTRIBUTION OF MONEY FLOWS FOR THE DEVELOPMENT OF INFORMATIONAL PARADIGM OF INDEPENDENT EVALUATION - Поздняков , Юрій; Лапішко , Марія; Гохберг , Ігор (Socio-economic relations in the digital society, 2019)
The article summarizes and interprets the results of the study of methodological error that arises when calculating the value of objects of independent evaluation by the method of indirect capitalization in the most general case, when the forecast period of future income streams discounting is not the integer number of time periods. The possibility of using the results of previous researches of authors as a theoretical basis for the development of a general theory of independent evaluation based on an information paradigm built on the regularity of information theory and error theory is considered. The authors in previously published papers [6–9] improved the method of determining the value of real estate with the help of the yield approach by the method of indirect capitalization of NOI, calculated the quantitative values of the studied absolute and relative methodological error. The effect of this error is completely offset by making an appropriate correction to the obtained result. The result obtained after calculations when performing the assessment is approximate, and the degree of its reliability is objectively determined by the decrease of the entropy of the object of evaluation – that is, the degree of uncertainty of its characteristics, which is numerically equal to the amount of received measuring information. Accordingly, in order to determine the accuracy of the result of economic variables measuring, a universal measure of the amount of received information may be applied, or the measures derived from it – may be an entropy error or informative value of the measuring result. According to the theory of information, any processes of selection, transmission, transformation of information can be described mathematically by using a universal entropy measure, and it is completely justified for the field of economic measurings. It will be appropriate to assume that in the future, with the passage of time, the information approach will be more and more widely used in the field of independent evaluation of value.